TAX SOCIALIZATION, SERVICE QUALITY AND TAXPAYER LOYALTY: PUBLIC TRUST AS A MEDIATING VARIABLE IN TANGGAMUS REGENCY, LAMPUNG - Alvindra Alvindra; Intan Fitri Meutia; Dedy Hermawan (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2026)
Tax compliance and taxpayer payment loyalty are essential for the sustainability of taxation systems and are closely shaped by the quality of interactions between tax authorities and taxpayers. This study examines the influence of service quality and tax socialization on taxpayer payment loyalty, with public trust serving as a mediating variable. Employing a quantitative explanatory research design, data were gathere through structured questionnaires distributed to taxpayers in Tanggamus Regency, Lampung Province. The data were analysis using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with bootstrapping techniques to assess both direct and indirect relationships among the research variables. The findings indicate that Service Quality has a positive and significant effect on Kepercayaan publik and Taxpayer Payment Loyalty. Furthermore, Kepercayaan publik significantly mediates the relationship between Service Quality and Taxpayer Payment Loyalty, highlighting the pivotal role of trust as a key mechanism in fostering sustainable tax compliance. In contrast, Tax Socialization demonstrates a significant direct effect on Taxpayer Payment Loyalty but does not have a significant effect on Public Trust, nor does it produce a mediating effect through trust. These results suggest that tax socialization activities that are predominantly technical and one-way are insufficient to build taxpayer trust. Overall, this study underscores the importance of consistently improving service quality and strengthening institutional trust as primary strategies to enhance taxpayer loyalty. The findings contribute to the literature on public administration, tax compliance behavior, and institutional trust within the context of public finance.